Microplastic particles in the Persian/Arabian Gulf – A review on sampling and identification. (May 2020) - Uddin, Saif; Fowler, Scott W.; Saeed, Talat
Abstract: Microplastics are ubiquitous, persistent pollutants that are reported in abundance within the marine environment. Their presence in seawater and marine sediments poses a legitimate environmental and ecological concern for toxicity and food chain transfer via marine organisms. Their capability for sorption of other hydrophobic contaminants and the inability of the wastewater treatment plants to completely remove them pose additional risks. This review highlights the methodologies for sampling, sample preparation, and identification used in the Persian/Arabian Gulf region, which is possibly one of the least studied marginal seas with only sixteen papers published on microplastics. The review highlights the several orders of magnitude variations in microplastic concentrations among different studies; e.g. in seawater, only 12 microplastic particles were reported from 40 transects of one km length in Kuwait to 0.71 microplastics m −3 in Qatar. Concentrations in beach sediments also show the significant difference between the northern and southern Gulf coasts, with 13 particles in 24 samples reported in Qatar, and 15 particles within 44 samples across Kuwait, to 3252 ± 2766 particles m −2 from Bandar Abbas, Iran. The biota samples also show similar variances, with only three particles identified from 87 gut samples in Kuwait to 828 particles in 58 samples that include 46 fish and 12 shrimps from Iran. Some extremely high concentrations in biota are also reported from Iran, with concentrations as high as 0.251 particles g −1 of muscle and 0.931 particles g −1 in gills. It is evident that there is no consensus in the Gulf region on the sampling techniques (mesh size of plankton nets and sieves), use of fluidization solutions and very different units used in data reporting such as particles m −3 and particles m −2 in water samples. In sediments units like particles g −1 and particles m −2 have been used, and for biota it is the number of particles present in the sample, while others have quantified data as particles g −1 of tissue. Considering the higher densities of PET, PVC, nylon and polyester than seawater, they are likely to migrate downwards into marine sediments, a transfer process that has not been studied in detail. Thus the review underscores the need to adopt harmonized protocols for microplastic studies in the region, and identifies certain aspects of microplastics that require further study. Highlights: Omnipresence of microplastics in Gulf marine and coastal environments is established. Little effort has gone into investigating microplastics in the Persian/Arabian Gulfmarine pollutants. Compares methodologies used for microplastic studies in the Gulf region The heavier microplastics quickly sink to the sediments. Use of acid digestion can degrade microplastics and result in erroneous determination.